1983
DOI: 10.1007/bf00238778
|View full text |Cite
|
Sign up to set email alerts
|

Identification and input-output properties of bulbar reticular neurons involved in the cerebral cortical control of trigeminal motoneurons in cats

Abstract: Neurons found in the medial bulbar reticular formation were activated by stimulation of the orbital gyrus and responded with antidromic spike potentials to selective stimulation of either the masseter or anterior digastric motoneuron pool in the trigeminal motor nucleus in cats anesthetized with alpha-chloralose. These two kinds of reticular neurons were assumed to be inhibitory neurons projecting to masseter motoneurons (IM neurons) and excitatory neurons projecting to anterior digastric motoneurons (ED neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…As described in the introduction, the masticatory CPG model also includes a relay between the medial components of the CPG and trigeminal motoneurons, because the former have few direct connections with the trigeminal motor nucleus (Mizuno et al ., 1978; Nozaki et al ., 1983; Landgren et al ., 1986; Fort et al ., 1994; Fay & Norgren, 1997; Kolta et al ., 2000). However, medial brainstem nuclei (Rgc, nParv and nPontc) do project strongly to adjacent lateral brainstem areas (the reticular formation surrounding the trigeminal motor nucleus and nParv‐α/subnucleus γ of the oral nucleus of the spinal trigeminal tract (nVspo‐γ); Fort et al ., 1994; Kolta et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in the introduction, the masticatory CPG model also includes a relay between the medial components of the CPG and trigeminal motoneurons, because the former have few direct connections with the trigeminal motor nucleus (Mizuno et al ., 1978; Nozaki et al ., 1983; Landgren et al ., 1986; Fort et al ., 1994; Fay & Norgren, 1997; Kolta et al ., 2000). However, medial brainstem nuclei (Rgc, nParv and nPontc) do project strongly to adjacent lateral brainstem areas (the reticular formation surrounding the trigeminal motor nucleus and nParv‐α/subnucleus γ of the oral nucleus of the spinal trigeminal tract (nVspo‐γ); Fort et al ., 1994; Kolta et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Only one third of the neurons in our study responded to stimulation of the inferior alveolar nerve, which contains primary afferents from the lower jaw and lip. The relatively long latencies of these responses confirm earlier work in the cat (Nozaki et al ., 1983; Sahara et al ., 1996), and suggest that the pathways are at least disynaptic. In contrast, almost all neurons (> 90%) located in the reticular nuclei around nVmot and in nVspo‐γ are excited by orofacial afferents at monosynaptic latencies (Eisenman et al ., 1963; Dallel et al ., 1990; Donga & Lund, 1991; Westberg & Olsson, 1991; Inoue et al ., 1992; Westberg et al ., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of medial nuclei excites digastric motonuerons and inhibits masseteric motoneurons at very short latency, 145 and medial RF neurons can be antidromically activated by stimulation of n. V mot. 137 On the other hand, anatomical studies have not provided much evidence that medial reticular areas have a strong monosynaptic projection to V motoneurons, suggesting that the rhythm generators act mainly via other groups of premotor neurons close to n. V mot. This point of view has been expressed in several papers from the group at UCLA.…”
Section: Figurementioning
confidence: 99%
“…Yasui et al (19851, who made cortical injections of wheat germ agglutinin (WGA)-HRP into the rostra1 part of the orbital gyrus, described anterogradely labeled fibers in the medial aspect of Vo.r and its adjacent reticular formation, and Qlsson and and Westberg and Qlss,on (1991) also reported that Vo.r interneurons responding to inferior alveolar or lingual nerve inputs also receive monosynaptic inputs from corticobulbar tract cells in the coronal gyrus. In addition, disynaptic excitation of digastric motoneurons by orbital gyrus stimulation has been described (Nakamura et al, 19751, although the location of the relevant premotoneurons has been reported to be the gigantocellular tegmental field (Takatori et al, 1981, Nozaki et al, 1983.…”
Section: Functional Properties Of Vo Neuronsmentioning
confidence: 99%